Application of volatilomics for meat quality, authenticity, and adulteration detection - Jin-Kyu Seo; Jeong-Uk Eom; Han-Sul Yang (Applied Food Research, 2025)
Volatile compound analysis has been increasingly utilized in the assessment of meat authenticity, adulteration detection, and quality evaluation. Volatile profiles are influenced by various factors, including species, diet, muscle type, and processing methods; nevertheless, pattern-based differentiation using multivariate statistical approaches has shown potential for distinguishing meat species, even under complex or processed conditions. Techniques such as solid-phase microextraction coupled with gas chromatography-mass spectrometry (SPME-GC-MS), in combination with chemometric tools, are commonly applied to identify species-associated volatile markers and detect undeclared meat adulteration. Volatilomics is particularly suitable for thermally processed products where conventional DNA- or protein-based techniques may be limited due to molecular degradation. Furthermore, the generation of specific volatile compounds associated with lipid oxidation or microbial metabolism supports its utility in monitoring quality-related attributes, including spoilage. However, the lack of standardized protocols and the difficulty of absolute quantification remain limiting factors. This review synthesizes recent advances in meat volatilomics and discusses the methodological challenges and future research directions needed to enhance its applicability across diverse meat matrices.